Role of Health Information Technologies in the Patient-Centered Medical Home - Kraschnewski, Jennifer L. (Diabetes Technology Society, 2013)
A national effort to reform primary care, known as the Patient-Centered Medical Home (PCMH), requires fulfillment of six standards determined by the National Committee for Quality Assurance to (1) enhance access and continuity, (2) identify and manage patient populations, (3) plan and manage care, (4) provide self-care and community support, (5) track and coordinate care, and (6) measure and improve performance. Information technologies play a vital role in the support of most, if not all, of these standards. However, given the newness of the PCMH, little is known on how health information technologies (HITs) have been employed to accomplish these objectives. This article will review the role of HITs, including electronic health records, web-based patient portals, telemedicine, and patient registries, with a focus on diabetes care, and how these technologies have been engaged in the establishment of the PCMH. In addition, we will discuss the benefits and potential risks and barriers to employing these technologies, including privacy and security concerns, as well as describe next steps for future work in this important area.